Profitability Drivers and Firm Value in Indonesian State-Owned Banks: The Moderating Role of Firm Size - Herdian Wibawa; Jaja Suteja; Atang Hermawan (Al-Qalam Institue, 2026)
This study examines the determinants of profitability, the effect of profitability on firm value, and the moderating role of firm size in Indonesian state-owned banks. State-owned banks are strategically important because their financial performance supports intermediation, public confidence, and national economic development. During 2014-2024, these banks faced regulatory change, digitalization, pandemic disruption, credit restructuring, and uneven profitability recovery. This quantitative causal ex-post facto study used secondary data from five state-owned banks listed on the Indonesia Stock Exchange, producing 55 bank-year observations. Panel-data regression and moderated regression analysis were conducted using EViews 13 at a 5% significance level. Liquidity positively affected profitability. Leverage also had a positive effect on profitability. Credit risk significantly reduced profitability and emerged as the most urgent managerial concern. Asset growth positively contributed to profitability. BOPO significantly reduced profitability, confirming the importance of operating efficiency. Profitability significantly increased firm value, while firm size strengthened this relationship as a quasi moderator. These findings emphasize integrated liquidity, funding, credit-risk, growth, and efficiency management. They also provide guidance for managers, regulators, and investors in strengthening sustainable performance and market valuation.